Directive and expressive speech acts in king’s choice game chat: A cyberpragmatic analysis - Agus Eko Cahyono; Putri Rahmawati Nur Afifah; Raudatul Nurul Insan (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the use of directive and expressive speech acts within the digital communication context of the mobile game King’s Choice, with a particular focus on how players interact across alliance, team, and kingdom chats. The investigation is theoretically grounded in Searle’s (1969) speech act theory-specifically his taxonomy of directive and expressive illocutionary acts-and Yus’s (2001, 2011) framework of cyberpragmatics, which provides analytical tools for understanding how online communication is shaped by multimodality and platform-specific affordances. Employing a qualitative descriptive methodology, the study analyzes 38 excerpts extracted from naturalistic in-game chat logs. The analysis reveals that directive speech acts manifest in various forms, including requests, commands, suggestions, advice, warnings, and prohibitions. Pragmatically, these directives serve to coordinate collective strategies, delegate in-game responsibilities, and maintain group cohesion during competitive events. Expressive speech acts are identified as apologies, compliments, expressions of joy, disappointment, regret, anger, and hope. These expressives function centrally in managing emotional states and negotiating interpersonal relationships within the game’s socially competitive environment. Notably, both speech act categories are frequently mediated by multimodal elements-such as emojis and stickers-which modulate illocutionary force and convey paralinguistic cues otherwise absent in text-based chat. This study extends extant research on platform-mediated communication by demonstrating how directive and expressive speech acts simultaneously fulfil strategic coordination and social bonding functions. In doing so, it highlights the interplay between linguistic pragmatics, multimodal affordances, and digitally situated interaction in contemporary gaming contexts.